Archie #18 - Vigoda, Bill; Woggon, Bill; Montana, Bob (Archie Comics, 2012)
"Negative Psychology." The students of Riverdale High are nominating worthy class presidents - so how did Archie's name get into the mix? He's stuck running for election despite the overwhelming disdain for his nomination. Now Jughead has to work overtime to stop his best pal from receiving any votes! Can they put a halt to his unwanted campaign? As an added trivia bonus, this is the final comic under the MLJ banner. Be sure to keep a lookout for the first appearance of the company as Archie Comics! Nearly 50 pages of quality stories! DISCLAIMER: The stories, characters, and incidents in this publication are entirely fictional. This publication contains material that was originally created in a less racially and socially sensitive time in our society and reflects attitudes that may be represented as offensive today. The stories are represented here without alteration for historical reference.